Layer-Selective Synthesis of MoS2 and WS2 Structures under Ambient Conditions for Customized Electronics - Park, Seoungwoong; Lee, Aram; Choi, Kwang-Hun; Hyeong, Seok-Ki; Bae, Sukang; Hong, Jae-Min; Kim, Tae-Wook; Hong, Byung Hee; Lee, Seoung-Ki (AMER CHEMICAL SOC, 2020)
Transition metal dichalcogenides (TMDs) have attracted significant interest as one of the key materials in future electronics such as logic devices, optoelectrical devices, and wearable electronics. However, a complicated synthesis method and multistep processes for device fabrication pose major hurdles for their practical applications. Here, we introduce a direct and rapid method for layer-selective synthesis of MoS2 and WS2 structures in wafer-scale using a pulsed laser annealing system (lambda = 1.06 mu m, pulse duration similar to 100 ps) in ambient conditions. The precursor layer of each TMD, which has at least 3 orders of magnitude higher absorption coefficient than those of neighboring layers, rigorously absorbed the incoming energy of the laser pulse and rapidly pyrolyzed in a few nanoseconds, enabling the generation of a MoS2 or WS2 layer without damaging the adjacent layers of SiO2 or polymer substrate. Through experimental and theoretical studies, we establish the underlying principles of selective synthesis and optimize the laser annealing conditions, such as laser wavelength, output power, and scribing speed, under ambient condition. As a result, individual homostructures of patterned MoS2 and WS2 layers were directly synthesized on a 4 in. wafer. Moreover, a consecutive synthesis of the second layer on top of the first synthesized layer realized a vertically stacked WS2/MoS2 heterojunction structure, which can be treated as a cornerstone of electronic devices. As a proof of concept, we demonstrated the behavior of a MoS2-based field-effect transistor, a skin-attachable motion sensor, and a MoS2/WS2-based heterojunction diode in this study. The ultrafast and selective synthesis of the TMDs suggests an approach to the large-area/mass production of functional heterostructure-based electronics.
Keywords: WAFER-SCALE SYNTHESIS; 2-DIMENSIONAL MATERIALS; THIN-FILMS; LARGE-AREA; GRAPHENE; GROWTH; TRANSISTORS; SENSOR; ARRAY